ANALYZING CODE-SWITCHING IN GEORGE BERNARD SHAW’S PYGMALION - Anita Anita (ELITE JOURNAL, 2019)
This paper is identifying the factors that cause code-switching among the characters in George Bernard Shaw’s work, Pygmalion. The method used in this research is descriptive analysis method starting from collecting data, organizing them based on classification, then analyzing them. The result shows that the condition of speakers, listeners, changes from formal to informal, changes the topic of conversation are the causes of code-switching which can be seen from the dialogue in the drama. The author found code swithcing corpus that occurred because of the differences of status, education, relationship, and purposes. The form of speech covers the aspect of sociolingustics, pragmatics, variety of language, speech act, registers, and rhetorics.